2015
DOI: 10.1371/journal.pone.0131227
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Relationship between Leishmania aethiopica and Leishmania tropica Revealed by Comparing Microsatellite Profiles

Abstract: Background Leishmania (Leishmania) aethiopica and L. (L.) tropica cause cutaneous leishmaniases and appear to be related. L. aethiopica is geographically restricted to Ethiopia and Kenya; L. tropica is widely dispersed from the Eastern Mediterranean, through the Middle East into eastern India and in north, east and south Africa. Their phylogenetic inter-relationship is only partially revealed. Some studies indicate a close relationship. Here, eight strains of L. aethiopica were characterized genetically and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…The phylogenetic analysis using hierarchical clustering framework with complete linkage revealed that strains belonging to the same species and species belonging to a sub-genus generally grouped together, although some exceptions were seen ( Figure 2B). The species L. tropica and L. aethiopica formed a subgroup that suggested close association between them, a finding consistent with what previously been reported in a comparative analysis performed using microsatellite markers (Krayter et al 2015). Similarly, the L. donovani complex containing L. infantum and L. donovani were assigned to a single clade, signifying their genomic similarity as reported previously (Lukes et al 2007).…”
Section: Resultssupporting
confidence: 90%
“…The phylogenetic analysis using hierarchical clustering framework with complete linkage revealed that strains belonging to the same species and species belonging to a sub-genus generally grouped together, although some exceptions were seen ( Figure 2B). The species L. tropica and L. aethiopica formed a subgroup that suggested close association between them, a finding consistent with what previously been reported in a comparative analysis performed using microsatellite markers (Krayter et al 2015). Similarly, the L. donovani complex containing L. infantum and L. donovani were assigned to a single clade, signifying their genomic similarity as reported previously (Lukes et al 2007).…”
Section: Resultssupporting
confidence: 90%
“…Multilocus microsatellite typing (MLMT) was performed in silico by blasting the forward and reverse primer sequences on each genome using the BioNumerics software version 7.6.1 (Applied Maths, Sint-Martens-Latem, Belgium). In total, 12 independent microsatellite genetic markers specific to L. tropica (GA1, GA2, GA6, GA9n, LIST7010, LIST7011, LIST7027, LIST7033, LIST7039, LIST7040, 4GTG and 27GTGn) were used as previously described by Krayter and colleagues [13,14,15] and for eight L. aethiopica isolates [29]. Bayesian, distancebased and factorial correspondence analyses revealed two populations: India/Asia and Israel/ Palestine that were subdivided, respectively, into two and three subpopulations [14].…”
Section: Microsatellite Typingmentioning
confidence: 99%
“…In this study, we perform a comparative genome analysis of three novel L. tropica genomes: two recent (2014) clinical isolates representing the outbreak of CL in Lebanon and one historical isolate from Azerbaijan (1974), with previously generated genome sequence data from 16 isolates [18,19]. Notably, we integrated the 19 WGS data with a wide microsatellite based genotyping survey across over 160 L. tropica strains [14,15,29] contributing to rationalise comparative analyses of SNPs and CNVs as well as chromosome ploidy. This study provides new insights into the population structure and genomic diversity of L. tropica parasites and integrate these into a more global comparative framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…killicki ) is more prevalent in Morocco causing 30–40% of the CL cases in some districts [ 10 ]. Leishmania aethiopica is found exclusively in Africa and is considered as the main causative agent of CL in Ethiopia and Kenya [ 7 , 11 ]. Less frequently, CL can be also due to L .…”
Section: Introductionmentioning
confidence: 99%